Rural-urban migration: its effects on the family - Dahlan , H.M.; Hairi Abdullah, (Universiti Kebangsaan Malaysia, 1977)
This article lays focus on five aspects on rural-urban migration in Peninsula Malaysia. The first aspect deals with emerging patterns of migration. From these patterns, some conclusions are attempted regarding the various directions and trends in current rural-urban migration in the country. From observations on the patterns, directions, and trends of rural-urban migration, some tentative conclusions are made regarding the categories of out migrants and their concentration in urban areas. It is a sociological truism that migration has its effects on migrant families. A major concern of this article is to illustrate the possible effects of migration on the family structure, especially its implications on the development of family health.